A low cost digital heart and respiratory rate monitoring system: article / Mohd Hilmi Firdaus Zakaria - Zakaria, Mohd Hilmi Firdaus (2014)
This project aims to design a low cost and portable heart and respiratory rate monitoring system. The proposed monitoring system was combining both the heart and respiratory rate in one system. The heart rate monitoring system was using an infrared LED and photodiode for the pulse sensor while the respiratory rate monitoring system was using a thermistor as a sensor. The system has been tested for a group of students with an age between 20 to 25 years old for the functionality test. The data were recorded and has been compared with the standard heart and respiratory rate measurement for the same group age. Both heart and respiratory rate shows a normal measurement where the heart rate result was between 60 to 100 beats per minute (BPM) and the the respiratory rate result was between 12 to 18 breaths per minute (BPM). It shows that this proposed system are able to produce a reliable measurement data for both heart and respiratory rate monitoring system.